2021
DOI: 10.1371/journal.pmed.1003615
|View full text |Cite
|
Sign up to set email alerts
|

Bile acid synthesis, modulation, and dementia: A metabolomic, transcriptomic, and pharmacoepidemiologic study

Abstract: Background While Alzheimer disease (AD) and vascular dementia (VaD) may be accelerated by hypercholesterolemia, the mechanisms underlying this association are unclear. We tested whether dysregulation of cholesterol catabolism, through its conversion to primary bile acids (BAs), was associated with dementia pathogenesis. Methods and findings We used a 3-step study design to examine the role of the primary BAs, cholic acid (CA), and chenodeoxycholic acid (CDCA) as well as their principal biosynthetic precursor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 57 publications
2
54
0
Order By: Relevance
“…As abnormal alteration in BAs and their receptors have been observed in AD patients, BAs and their receptors have received extensive attention from researchers as biomarkers and potential targets for the diagnosis and treatment of AD. In the latest large-scale clinical study [103], researchers conducted three experiments to investigate whether abnormal cholesterol catabolism, through its conversion into BAs, is associated with the progression of AD and VD. First, they examined serum concentrations of CA, CDCA, and 7α-OHC in more than 1,800 participants from two prospective studies and used linear regression and mixed-effects models to examine their association with brain amyloid accumulation white matter lesions and brain atrophy.…”
Section: 2mentioning
confidence: 99%
“…As abnormal alteration in BAs and their receptors have been observed in AD patients, BAs and their receptors have received extensive attention from researchers as biomarkers and potential targets for the diagnosis and treatment of AD. In the latest large-scale clinical study [103], researchers conducted three experiments to investigate whether abnormal cholesterol catabolism, through its conversion into BAs, is associated with the progression of AD and VD. First, they examined serum concentrations of CA, CDCA, and 7α-OHC in more than 1,800 participants from two prospective studies and used linear regression and mixed-effects models to examine their association with brain amyloid accumulation white matter lesions and brain atrophy.…”
Section: 2mentioning
confidence: 99%
“…Thistrend was observed for other differential BAs, including CA, CDCA, THCA, HCA, UCA,UDCA, NorCA and GCDCA, although these differences did not reach statisticalsignificance. These results suggest that BA deficiency is an important feature forpatients undergoing METH withdrawal and that BA deficiency may influence neuronalfunctions and enhance the risk of dementia ( 41 ). In addition, serum and fecal BA concentrations were shown todecrease in patients of irritable bowel syndrome with constipation ( 42 ).…”
Section: Discussionmentioning
confidence: 98%
“…Our previous studies demonstrated perturbations in a prodromal mouse model of PD to include both brain ( Graham et al, 2018b ) and blood ( Graham et al, 2018a ), while our most recent study reported disturbances in the gut microbiome of PD sufferers ( Li et al, 2021 ). The gut-brain axis has been receiving a lot of attention in recent years, specifically how it relates to neurodegenerative disease ( Peterson, 2020 ; Agus et al, 2021 ; Varma et al, 2021 ); herein and for the first time, combining metabolomics and epigenetics approaches, we highlight bile acid metabolism as being the major biochemical pathway to be perturbed in the brain of those people who died from PD as compared with controls. The interplay between these specific methylation changes and their correlating metabolites may have a direct impact on the pathogenesis of PD.…”
Section: Discussionmentioning
confidence: 99%